Effect of incorporation of zinc oxide nanoparticles on properties of PEMA based polymer electrolyte. (2021) - Sachdeva, Amit; Singh, Shruti; Singh, Pramod K.
Abstract: High performance Polymer electrolytes are widely discussed nowadays on account of their physical and electrochemical properties. The present work involves modification of structural and electrical properties of PEMA based plasticised polymer electrolyte by incorporation by nano sized zinc oxide nanoparticle. It has been observed that the overall value of conductivity increased almost by 100 times when varying concentration of zinc oxide nanoparticles was added to matrix. Complex Impedence spectroscopy was used to measure the conductivity of the fabricated nano composites using various cole–cole plot. Perfect complexations among various components are affirmed by FTIR studies while XRD confirmed the variation in crystallinity of the prepared sample. Surface morphology of the samples was studied using Scanning Electron Microscopy.